Coated monolithic catalysts for better selective catalytic reduction: Concerns about structural integrity, catalytic activity and anti-poisoning performance - Yidan Huang; Zhihao Yu; Mingyu Guo; Hao Liu; Xianbin Liu; Jinfeng Han; Shaoping Cui; Boqun Liu; Yingjie Zhao; Jinqiu Wei; Bin Liu; Siqi Chen (Catalysis Communications, 2023)
Rational development of high-performance catalysts for selective catalytic reduction (SCR) is important for NOx removal. As the most widely used commercial catalysts, coated monolithic catalysts need to adapt to the harsh external conditions, which make researchers concerned about maintaining structural integrity, catalytic activity, and toxicity resistance in services. Herein, we seek solutions by clarifying the influences of coating process parameters on these three concerns, and trying to tackle the technical difficulties of coated monolithic catalysts in SCR applications. The insights presented in this paper are beneficial to the synthesis optimization and engineering innovations for SCR catalysts.